The witches : Salem, 1692 - Schiff, Stacy (Little, Brown and Company, 2015)
The Pulitzer Prize-winning author of Cleopatra analyzes the Salem Witch Trials to offer key insights into the role of women in its events while explaining how its tragedies became possible.